Research methods in clinical psychology : an introduction for students and practitioners - Barker, Chris, 1948-; Pistrang, Nancy; Elliott, Robert, 1950- (Malden, MA : John Wiley and Sons, Inc., 2016)
"Offers a comprehensive introduction to the various methods, approaches, and strategies for conducting research in the clinical psychology field"--
Machine generated contents note: The Research Process -- Philosophical Issues -- What is Research? -- What is Science? -- Social and Political Issues -- Professional Issues -- The Intuitive Practitioner -- The Scientist-Practitioner -- The Applied Scientist -- The Local Clinical Scientist -- The Evidence-Based Practitioner -- The Clinical Scientist -- The Practice-Based Evidence Model -- Comparison of Models -- Implications for Clinical Training -- Personal Issues -- Why Do Clinical Psychologists Do Research? -- Why Don't Clinical Psychologists Do Research? -- Weighing up the Pros and Cons of Doing Research -- Chapter Summary -- Further Reading -- Questions for Reflection -- Formulating the Research Questions -- Choosing the Topic -- Developing the Questions -- Hypothesis-testing versus Exploratory Research Questions -- Some Types of Research Question -- Literature Review -- The Proposal -- Funding -- The Politics of Research in Applied Settings -- Access -- Responding to Doubts -- Authorship -- Chapter Summary -- Further Reading -- Questions for Reflection -- The Process of Measurement -- Domains of Variables -- Measuring Psychological Constructs -- Measurement Sources and Approaches -- Foundations of Quantitative Methods -- Positivism -- Psychometric Theory -- Definitions -- Reliability -- Reliability Statistics -- Validity -- Generalizability Theory -- Item Response Theory -- Utility -- Standards for Reliability and Validity -- Chapter Summary and Conclusions -- Further Reading -- Questions for Reflection -- Historical Background -- Philosophical Background -- Phenomenology -- Social Constructionism -- Families of Qualitative Approaches -- Thematic Analysis Approaches -- Narrative Approaches -- Language-Based Approaches -- Ethnographic Approaches -- Ways of Evaluating Qualitative Studies -- Conclusion: Choosing and Combining Methods -- Chapter Summary -- Further Reading -- Questions for Reflection -- Mode of Administration -- Open-ended and Closed-ended Questions -- Qualitative Self-report Methods -- Types of Qualitative Interview -- Interview Schedule -- Interviewing Style -- Quantitative Self-report Methods -- Questionnaire Design -- Chapter Summary -- Further Reading -- Questions for Reflection -- Qualitative Observation -- Participant Observation -- Text-based Research -- Quantitative Observation -- Background -- Procedures for Conducting Observations -- Reliability and Validity Issues -- Chapter Summary -- Further Reading -- Questions for Reflection -- Nonexperimental Designs -- Descriptive Designs -- Correlational Designs -- Experimental Designs -- Cook and Campbell's Validity Analysis -- Nonrandomized Designs -- Randomized Designs -- Conclusion: Choosing a Research Design -- Chapter Summary -- Further Reading -- Questions for Reflection -- Historical Background -- Single-case Experimental Designs -- Procedure -- AB Design -- Reversal (or ABAB) Design -- Multiple-baseline Design -- Changing-Criterion Design -- Data Analysis -- Generalization -- Naturalistic Case-study Designs -- Narrative Case Studies -- Systematic Case Studies -- Time-Series Designs -- Conclusion -- Chapter Summary -- Further Reading -- Questions for Reflection -- Sampling -- The Target Population -- Bias and Representativeness -- Sample Size -- Alternative Approaches to Sampling and Generalizability -- Summary and Conclusion -- Ethical Issues -- Informed Consent -- Harms and Benefits -- Privacy and Confidentiality -- Ethics Self-study Exercise -- Ethics Committees -- Chapter Summary -- Further Reading -- Questions for Reflection -- What is Evaluation? -- The Sociopolitical Context -- Preparation for Evaluating a Service -- Aims and Objectives -- The Impact Model -- The Target Population -- Estimating the Extent of the Target Problem in the Target Population -- Needs Assessment -- Delivery System Design -- Monitoring the Process of Service Delivery -- Coverage and Bias -- Service Implementation -- Outcome Evaluation -- Client Satisfaction Surveys -- Patient focused Research and Outcomes Management -- Cost-effectiveness -- Chapter Summary -- Further Reading -- Questions for Reflection -- Qualitative Data Analysis -- Within-case and Cross-case Analysis -- Preliminaries to Qualitative Data Analysis -- Processes in Qualitative Data Analysis -- Good Practice in Qualitative Analysis -- Quantitative Data Analysis -- Data Entry -- Data Checking -- Data Reduction -- Data Exploration -- Statistical Significance Testing for Answering the Research Questions -- Analyzing the Strength and Significance of Quantitative Effects -- Interpretation -- Contributions to Knowledge: Understanding the Meaning of the Findings -- Methodological Issues: Strengths and Limitations of the Study -- Scientific and Practical Implications -- Dissemination -- Writing up -- Publication -- Authorship Issues -- Utilization -- The End -- Chapter Summary -- Further Reading -- Questions For Reflection -- Methodological Pluralism -- Appraising Research -- Combining Research with Practice -- Some Images of Research -- Questions for Reflection.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Clinical psychology -- Research -- Methodology; Counseling -- Research -- Methodology; Psychotherapy -- Research -- Methodology; PSYCHOLOGY -- Clinical Psychology; Clinical psychology -- Research -- Methodology; Counseling -- Research -- Methodology; Psychotherapy -- Research -- Methodology; Psychology, Clinical -- methods; Electronic books